Water Resources Management in Progo River Basin using SWOT Analysis - Neil Andika; Ni Made Candra Partarini (Journal of the Civil Engineering Forum, 2023)
About 3.1 million people use the water from Progo River for domestic use, agriculture, livestock and even for religious rituals which solidifies the importance of Progo River to the residence. However, the characteristics of the Progo River has not been studied well. This paper aims to understand the characteristics of the Progo River and the main threat to the river. To achieve those objectives, a SWOT analysis was used particularly in three segments of Progo River Basin, which is upstream, midstream, and downstream reach. The upstream segment has a basin slope more than 25%, the middle segment has a basin slope of 8-25%, and the downsteam segment has a basin slope less than 8%. The SWOT analysis would be based on desk study, hydrological analysis, water quality analysis and field observation. The upstream segment is characterized by high land erosion rate, steep slope, and the presence of Umbul Jumprit, a holy site for Buddhism. The midstream segment is very close to the residence area which reduces the water quality of the river. Furthermore, some scouring issues and flooding risk have become the main concern in this area. The downstream segment is crossed by several bridges of national roads while also having a gravel mining activity. This activity causes a massive scouring problem to the structures. It is clear that the main threat to the Progo River Basin is volcanic and human activities. For a starter, the government should prioritize the revitalization act in the upstream area which has a great impact on the midstream and downstream areas. Because SWOT analysis from water resources management perspective have never been done in the Progo River Basin, these findings can be served as a foundation for the integrated water resources management in the basin.